Sustainable storage of Cocoyam Cormels using Ash lined clay pits for post harvest preservation - Linus Oriaku; Cyprian N. Tom; Ifiok Ekop; Leonard Akuwueke; M. F. Umunna; Inemesit Ekop; George Uwadiegwu Alaneme; James Ehiem; Emmanuel Ubuoh; Macmanus Chinenye Ndukwu (Scientific Reports)
Abstract This study evaluated the efficacy of plant-derived ash treatments on cocoyam cormels’ storage life and nutritional quality. A novel underground cellar with composite walls comprising clay and plant material ash was developed. Various ash treatments, including Iroko tree bark (IR) and feathery Pennisetum Grass (G2), significantly reduced moisture uptake and weight loss (< 28% and 28.98%, respectively) compared to ambient storage (60% weight loss). IR treatment exhibited a lower average temperature and higher thermal gradient. G2 treatment demonstrated a balanced nutritional profile, with low moisture content (9.85%), high dry matter (90.15%) and maintains stable crude protein levels, minimizes protein breakdown, and preserves starch, resulting in high carbohydrate content (77.62%).Principal Component Analysis (PCA) confirmed G2’s balanced nutrient composition and minimal moisture uptake. Statistical analysis revealed significant treatment effects on temperature difference and mass loss. These findings suggest that specific plant-derived ash treatments can enhance cocoyam cormels’ storage life and maintain nutritional quality, offering a promising solution for post-harvest storage.